Multi-virulence of Campylobacter jejuni carried by chicken meat in Brazil - Peres, Phelipe Augusto Borba Martins; de Melo, Roberta Torres; Armendaris, Paulo Marcel; Barreto, Fabiano; Perin, Tiago Follmann; Grazziotin, Ana Laura; Monteiro, Guilherme Paz; Buiatte, Ana Beatriz Garcez; Mendonça, Eliane Pereira; Lourenzatto, Eduarda Cristina Alves; Bicalho, Artur Slompo Muniz; Filho, Marcelo de Vito; et al. (Frontiers in Microbiology, 2023)
Campylobacter jejuni is the most frequent cause of bacterial gastroenteritis; therefore, the characteristics of its epidemiology must be continuously investigated to support possible mitigating measures. This is particularly important when evaluating representative strains from the world's leading chicken meat exporter, Brazil. We evaluated a panel of 14 virulence genes in 359 strains of C. jejuni isolated from chilled broiler carcasses in Brazil. The genes were classified into five virulence categories (B: biofilm/motility; SS: secretion/cytotoxicity system; CI: invasion/colonization; GB: Guillain-Barré; and AE: adaptation to stress). The percentage of strains with stress adaptation genes (86.07%) indicates the ability to survive in unfavorable environments; in addition, the strains showed a risk of causing infections in humans due to the frequency of the hcp gene (97.77%). Genes related to Guillain-Barre syndrome (GBS) in 77.44% of strains are an additional concern, which must be monitored. The gene panel showed the presence of 124 virulence profiles. Individual analyses by carcass, slaughter establishment, and municipalities in which they were located showed high index variabilities (I.Var.) of 0.82, 0.87, and 0.78, respectively. Georeferencing indicated the state of Paraná as a hotspot for virulent strains. Higher levels of isolation and multi-virulence were identified in the summer, which is hot and humid in Brazil. Together, our results showed that the studied strains are a potential danger to public health and that there is an urgent need for their surveillance and the adoption of control measures, especially in the state of Paraná.